Landasan Filosofis Pendidikan Kristen dan Relevansinya pada Masa Kini - Yohanes Telaumbanua (Jurnal Arrabona, 2024)
The background to this research is to provide a foundation for Christian religious education based on a philosophical basis. Understanding the principles and practices of Christian religious education requires a solid foundation in eroding the secular philosophy that greatly influences the church and students. So it does not achieve the goals of Christian religious education. because the philosophy that enters Christian religious education places great emphasis on the autonomy of reason rather than the authority of God as the causality of all things. Philosophy is very systematic and critical in drawing conclusions. It is not uncommon for this rationality to result in the Bible losing its place as the main source in explaining metaphysics, epistemology and axiology, which is replaced by logical thinking which often even opposes the contents of the Bible. So, through discussing the philosophical foundations of Christian education, it will contribute to the implementation of Christian education today. To find detailed data in this discussion, the author uses a qualitative method, a descriptive approach, the findings of this research are, the reviewer examines the meaning of the philosophical foundations of Christian Religious Education, to obtain results that can be applied in contemporary Christian education.